A green, hybrid cleaning strategy for the mitigation of biofouling deposition in the elevated salinity forward osmosis membrane bioreactor (FOMBR) operation. (February 2022) - Ab Hamid, Nur Hafizah; Wang, David K.; Smart, Simon; Ye, Liu
Abstract: Forward osmosis membrane bioreactors (FOMBRs) are currently gaining attention from the wastewater treatment industry, for their potential to produce high effluent quality and a relatively better flux stability against fouling. However, only using physical cleaning methods is not sufficient to recover the water flux performance satisfactorily under a long-term operation. This study comprehensively investigated the efficiency of a hybrid, environmentally-friendly cleaning strategy involving a combination of physical and free nitrous acid (FNA) cleanings under a long-term FOMBR operation. During 92 days of FOMBR operation, physical cleaning recovered the water flux by 85%, whilst FNA cleaning contributed to an additional 5% of the recovery. In addition, FNA cleaning also offered a retardation of fouling deposition by maintaining the water flux 18–30% more than that obtained by only the physical cleaning. A possible mechanism for FNA's role as the cleaning reagent was proposed for the first time in this study based on the water flux performance and membrane autopsy analysis. The results showed FNA cleaning broke down the residual fouling layer, preferencing protein-based substances. A lower ratio of protein to polysaccharides of the residual fouling layer contributed to a more negatively charged membrane surface (- 42.34 ± 0.30 mV) compared to the virgin one (- 17.54 ± 0.81 mV). This resulted in a stronger electrostatic repulsion between the foulants and the membrane surface, and thus slowed down the biofouling deposition process. This study suggested FNA solution has the great potential not only to recover the membrane performance, also as a strategy to slow down fouling deposition. Graphical abstract: Image 1 Highlights: FNA cleaning results in a more negatively charged membrane surface (- 42.34 ± 0.30 mV). Stronger electrostatic repulsion between foulants and membrane after FNA cleaning. FNA cleaning contributed to 90% of the overall water flux recovery of the membrane. A mechanism of reduced fouling due to FNA cleaning is proposed for the first time.